Social motivations of live-streaming viewer engagement on Twitch. (July 2018) - Hilvert-Bruce, Zorah; Neill, James T.; Sjöblom, Max; Hamari, Juho
Abstract: Little is known about the motivations underlying viewer engagement in the rapidly growing live-streaming multimedia phenomenon. This study trialled an eight-factor socio-motivational model, based on Uses and Gratifications Theory, to explain four aspects of live-stream viewer engagement. Cross-sectional data was collected through an international, online self-report survey of Twitch users ( N = 2227). Multiple and ordinal linear regression analyses identified six motivations which helped to explain live-stream engagement: social interaction, sense of community, meeting new people, entertainment, information seeking, and a lack of external support in real life. Compared to mass media, viewer motivations to engage in live-stream entertainment appear to have a stronger social and community basis. Furthermore, live-stream viewers who preferred smaller channels (<500 viewers) were more motivated by social engagement than viewers who preferred larger channels. These findings offer insight into the motivations for live-stream engagement, and help to lay a foundation for further research. Highlights: Live-stream viewer engagement was explored from a socio-motivational perspective. Social and community interaction motivated all types of live-stream engagement. Viewers who lacked external support spent more time watching live-streams. Small channel viewers were more socially motivated than larger channel viewers.